2008
DOI: 10.1128/aac.00110-08
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide Resistance and pncA Gene Mutations in Mycobacterium tuberculosis

Abstract: Thirty-four pyrazinamide-resistant and 37 pyrazinamide-susceptible Mycobacterium tuberculosis complex strains were analyzed for pncA gene mutations. None of the sensitive strains had any mutations, apart from silent mutations, whereas all but one resistant strain showed pncA mutations. By using sequencing as a means of early resistance detection, the inconsistency of phenotypic pyrazinamide assays can be circumvented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 22 publications
6
84
2
1
Order By: Relevance
“…In contrast, in our study 40% of the clinical isolates showed substitutions in rpsL gene but no alteration was found in rrs gene. Jureen et al in their study from Sweden observed many mutations for pncA gene [26], and in 2009, S S Prabhu et al from India had found many mutations in pncA gene at various codons [27], but we observed overall 35% frequency of the mutation at codon 195 of pncA gene. Mita et al 2008 from India had found reported and some novel mutation in embB [28].…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, in our study 40% of the clinical isolates showed substitutions in rpsL gene but no alteration was found in rrs gene. Jureen et al in their study from Sweden observed many mutations for pncA gene [26], and in 2009, S S Prabhu et al from India had found many mutations in pncA gene at various codons [27], but we observed overall 35% frequency of the mutation at codon 195 of pncA gene. Mita et al 2008 from India had found reported and some novel mutation in embB [28].…”
Section: Discussioncontrasting
confidence: 50%
“…Pyrazinamide is a prodrug that converted to pyrazinoic acid by the enzyme pyrazinamidase, encoded by the pncA gene in Mycobacterium strains. Mutations in pncA results to lost or reduced pyrazinamidase activity which leads to development of resistance [23]. In this experiment, after biofield treatment pyrazinamide reduced 31.4% resistance property in XDR strains besides increased susceptibility by four folds in case of MDR strains as compared to control ( Table 1).…”
Section: Citationmentioning
confidence: 80%
“…A comparable situation is found in the case of the resistance to PZA, another pro-drug which has pcnA as its activator. Mutations in this gene, encoding the amidase required to produce the active drug, Pyrazinoic acid (POA), accounts for a large fraction of the resistance in M. tuberculosis (Jureen et al, 2008). In spite of that, PZA resistant strains without mutation in pcnA have been reported (Raynaud et al, 1999).…”
Section: Efflux Pumps In M Tuberculosis Their Role In Tolerance To mentioning
confidence: 99%